Meningkatkan Hasil Belajar Siswa Melalui Penerapan Pendekatan Pemecahan Masalah (Problem Solving) pada Mata Pelajaran Matematika - Erni Erni (Universitas Cokroaminoto Palopo, 2018)
The purpose of this research is to find out the application of problem solving approaches to mathematics subjects in class V SDN 158 Watallipu and to find out the application of problem solving approaches can improve student learning outcomes. The approach used is a qualitative approach with the type of research used is Classroom Action Research (CAR). The results of the observation analysis of teacher activity in cycle I are in less qualification (K) and cycle II is in good qualification (B). The results of observations of student activities in the first cycle are in less qualification (K) and second cycle is in good qualification (B). Learning outcomes in the first cycle are in less qualification (K) because they have not reached the minimum completeness criteria caused by factors researchers lack guiding students to read story problems to completion to find out the type of problem and the researcher did not give students the opportunity to respond to the results obtained another group, because the first cycle was not successful, the study continued into cycle II with various improvements. Cycle II has an increase, namely being in good qualification (B) and has reached a predetermined indicator. The conclusion in this study is to apply the approach to problem solving (problem solving) can improve student learning processes and student mathematics learning outcomes.